Photocatalytic activity of cobalt and cerium doped bismuth-ferrite nanostructures synthesized by sol-gel auto-combustion method - Che Mohd. Zawawi, Che Zaheerah Najeehah (2020)
Large volumes of water and chemicals from textile industry are drained to the environment, which contain different non-biodegradable toxic organic compounds (dyes). These dyes require proper treatment prior to discharge into environment. Rhodamine B (RhB) is a widely used dye in textile industry which is harmful and carcinogenic in nature. Finding the efficient, rapid and cost-effective mechanism for the removal of these harmful dyes from wastewater is the major challenge. This study explores the potential of bismuth ferrite (BiFeO3) nanoparticles as photocatalyst for photocatalytic degradation of RhB dye in solution. The BiFeO3 nanoparticles were prepared by sol-gel auto-combustion method for the photocatalytic degradation of RhB dye. The optical, magnetic and structural properties of the BiFeO3 nanoparticles were tuned by introducing the dopants such as cobalt (Co) and cerium (Ce). The effect of dopants concentrations (Bi1-xCoxFeO3 and Bi1-yCeyFeO3; x and y = 0.1, 0.2, 0.3, 0.4 and 0.5) on the optical, magnetic and structural properties were determined by high-resolution transmission electron microscopy (HRTEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) together with energy dispersive X-ray (EDX), UV-Visible (UV-Vis) and vibrating sample magnetometer (VSM). The degradation of RhB dye was investigated and confirmed through UV-Vis spectroscopy, Fourier transform infrared (FTIR) spectroscopy and high-performance liquid chromatography (HPLC). The XRD analysis of synthesized doped BiFeO3 nanoparticles confirmed the presence of secondary phase (sillenite) along with primary phase in BiFeO3 nanoparticles. The percentage of sillenite phase was significantly increased with the increase in dopant ratios. The microscopic analysis of the BiFeO3 nanoparticles revealed nanosized irregular shape particles in range of 45-50 nm with agglomerated coalescence behaviour. Cobalt- doped BiFeO3 nanoparticles exhibited strong ferromagnetic behaviour. For cerium- doped BiFeO3 nanoparticles, high degradation rate was observed as compared to the cobalt- doped BiFeO3 nanoparticles. However, cerium- doped BiFeO3 nanoparticles possessed soft magnetic nature. The presence of dopant reduced the particle size and the optical band gap. The optical band gap of 2.2 eV was measured for pure BiFeO3 nanoparticles while for cobalt and cerium- doped BiFeO3 nanoparticles optical bandgaps were measured in range of 1.47-1.57 eV and 2.13-2.17 eV respectively. Cobalt and cerium- doped BiFeO3 nanoparticles successfully degraded RhB solution in less than 1 hour compared to pure BiFeO3 nanoparticles. The 0.3 doping concentration of cobalt and cerium was found to be the best for degradation of RhB solution. The Bi0.7Ce0.3FeO3 degraded the RhB solution immediately after the reaction started while Bi0.7Co0.3FeO3 nanoparticles required 25 minutes. The findings show the huge potential of cobalt and ceriumdoped BiFeO3 nanoparticles as photocatalyst for effective and rapid degradation of RhB dye.